2007
DOI: 10.1242/jcs.03409
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated receptor signalling, endocytic sorting and dysregulation in cancer

Abstract: Protease-activated receptors (PARs) are G-protein-coupled receptors (GPCRs) that are activated by a unique proteolytic mechanism. PARs play crucial roles in hemostasis and thrombosis, as well as in inflammation and vascular development. Coagulant proteases, which are generated at sites of vascular injury, act mainly through PARs to elicit signalling in a variety of cell types. Since PARs are irreversibly activated signalling must be tightly regulated. Desensitization and trafficking of proteolytically activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 87 publications
(85 reference statements)
3
121
0
Order By: Relevance
“…66 and reviewed in Refs. 3,67). Recently, it was reported that TLR4 activation results in sequential utilization of MyD88-and TRIF-dependent signaling (68).…”
Section: Discussionmentioning
confidence: 99%
“…66 and reviewed in Refs. 3,67). Recently, it was reported that TLR4 activation results in sequential utilization of MyD88-and TRIF-dependent signaling (68).…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modification by proteolytic cleavage has been recognized as an important mechanism for the functional modulation of a diverse array of cell surface proteins, such as Notch, protease-activated receptors (PARs) and many cell adhesion molecules [1][2][3]. Proteolytic modification of these molecules usually takes place in the secretory pathway or on the cell surface, mediated by proprotein convertases or sheddases such as furin, MMPs and ADAMs [4].…”
Section: Introductionmentioning
confidence: 99%
“…PAR1, PAR3 and PAR4 are activated by thrombin whereas PAR2 is a receptor for trypsin (1). In addition to thrombin, PAR-1 is also cleaved and activated by plasmin, activated protein C (APC), factor Xa, factor VIIa and the matrix metalloprotease MMP-1 (2). Once activated PARs couple to heterotrimeric G-proteins.…”
Section: Introductionmentioning
confidence: 99%